Enjeux de la mutation des techniques artisanales sur la formalisation de l’exploitation de l’or au Burkina Faso - Edith Sawadogo; Dapola Evariste Constant Da† (EchoGéo)
The formalization of artisanal gold mining is recommended by the World Bank, which considers that it promotes the minimization of harmful impacts. According to some authors, mechanization and the high level of the price of gold internationally are favorable to effective formalization. On the basis of documentary research and field surveys in the commune of Kampti in May 2018 and December 2019, we show that despite the willingness of actors to secure their investments through formalization, they come up against unfavorable institutional and legal realities. In the new perspective of formalizing gold sites by National Agency for the Supervision of Artisanal and semi-mechanized mining (ANEEMAS), the sidelining of key players in the marketing chain limits the effectiveness of the process of formalizing the activity.